A case report of severe myocarditis combined with erythema multiforme caused by herpes simplex virus-1 - Huang, Anwu; Lin, Bin; Ji, Xiaojun; Chen, Shanjiang (Frontiers in Cardiovascular Medicine, 2025)
Herpes simplex virus-1 (HSV-1) is a recognised pathogen that is primarily associated with skin mucosal infection. However, in rare cases, it has been observed to lead to skin extramucosal manifestations, including myocarditis. The present case report documents the occurrence of severe myocarditis in a 35-year-old female patient, attributed to HSV-1 infection. She received cardiac support in the form of VA-ECMO (Venoarterial Extracorporeal Membrane Oxygenation). Concurrently, the patient exhibited cutaneous manifestations of erythema multiforme, which demonstrated a favourable response to antiviral and hormonal therapy. This case underscores the significance of HSV-1 as a causative agent of myocarditis and underscores the necessity for vigilance and expeditious treatment of potential cardiac complications caused by HSV-1.